Patient Delay for Colorectal Cancer Patients in International Islamic University Malaysia Medical Centre - Kodiron, Muhammad Afiq; Aidid, Edre Mohammad; Elagili, Faisal; Md Nor, Azmi (2020)
BACKGROUNDS Many studies have highlighted the influence of diagnostic and therapeutic delays on the prognosis of patients with colorectal cancer (CRC). There are limited data on patient delays in presentation, diagnosis or treatment from east coast of Malaysia. OBJECTIVE The aim of our study to determine the waiting time for patients with CRC in IIUMMC. METHODS Between February 2017 to October 2019 data on patients with CRC were reviewed retrospectively. Patient demographic characteristics, day of first symptoms, day first visit to the doctor, day of colonoscopy, day of diagnosis, referral, the date of diagnosis, the stage of the tumor at diagnosis and the date of therapy was retrieved from hospital records. Patient waiting time is the time from first symptom to first consultation. Diagnosis waiting time is the time between seeking medical advice and the date of final diagnosis based on histopathological examination. Treatment waiting time is the time from the first patient-physician consultation until the first day of any form of treatment. RESULTS 41 patients (56% male) were recruited, the mean age was 60 years, cancer site was 39% in rectum, 36% in left colon and right colon in the remaining 24% of cases. The most commonly reported symptom was altered bowel habit (51%). 49% of patients were referred from Emergency Department. The majority (61%) of the cases were diagnosed as advanced stage (Stages III-IV). Patients who presented to clinic had symptoms for a median of 92 days prior to presentation. The patients waited for median 20 days for a pathologically confirmed diagnosis and median treatment waiting time was 30 days. CONCLUSION Patient delay was observed for our CRC patients. Further studies are needed to determine the reasons for these delays and could be reduced by improving information, health education and raising awareness of CRC-related symptoms.